Synthesis and Antibacterial Activities of Pleuromutilin Derivatives with Modified 7-Aminocephalosporin Acid and Thioether Moiety - Guo, A-Rong; Zhou, Hua-Hong; Dong, Kui-Kui; Wu, Kai-Qun; Wang, Yu-Liang; Chen, Tian (Asian Journal of Chemistry, 2012)
In order to study the effect of heterocyclic carboxamide group on pleuromutilin's antibacterial activity, seven novel pleuromutilin derivatives with modified 7-aminocephalosporin acid and thioether moiety were designed and synthesized. The antibacterial activities of the new compounds were tested via agar-well diffusion method in vitro under different concentrations. The results showed that three target compounds (5a, 5d, 5f) still had antibacterial activity against Staphylococcus aureus SC and Staphylococcus aureus ATCC26112 at the concentration 2.0 μg/ mL.